A feastful of islands ; Prisoners ; Monique's new voice [videorecording] - Canlas, Ruben, Jr; Cantada, Candy; Lazaro, Cheche; Ortigas, Marga (The Probe Team, 1995)
Investigates the Spratly Islands conflict; the forty eight Muntinlupa prisoners in their forty one days hunger strike calling themselves political prisoners and an interview with singer Monique Wilson.